17 Consider The Following Sum Of Products Expression F. The Equivalent Product Of Sums Expression Is (3 Points) F - ABC + A'B'C + AB'C + A' BC + A'B'C' F = (A + B + C) + (A' + B' + C) + (A + B + C) + (A' + B + C) + (A' + B + C') F = (A + B + C)(A' + B+)(A

匿名用户 最后更新于 2021-11-29 17:10 计算机类Computing


17 Consider the following Sum of Products expression F. The equivalent Product of Sums expression is (3 Points) F - ABC + A'B'C + AB'C + A' BC + A'B'C' F = (A + B + C) + (A' + B' + C) + (A + B + C) + (A' + B + C) + (A' + B + C') F = (A + B + C)(A' + B+)(A' + B' + C) F = (A + B' +C)(A' + B+C)(A' + B' + C) F = (A + B + C) + (A' + B' + C) + (A + B' + C) + (A' + B + C)

已邀请: